War disasters and their effects on urban structure - abduljaleel Ibrahim, Mustafa; Abdulaziz Jabur, Tarq (Journal of Planner and Development, 2019)
Many urban and rural areas fall under the impact of disasters, whether natural or industrial, and with increasing complexity in urban areas, with diversity of economic, social and political components, and technological and cognitive development, the effects of disasters and wars have increased with the time, where disasters are affecting all aspects of life, causing great waste of property and lives, also displacement of populations and disruption of economic life, these effects are multiplied if they are not dealt with in sound curricula and scientific strategies.The research aims to identify the experiences of some countries and their strategies and effective programs in reconstruction after exposure to disasters and wars within urban areas, using the descriptive and analytical approach to disaster management in urban areas, As part of the countries' effective efforts to overcome the effects of disasters on the urban infrastructure of various components. Assuming that the experience of some countries in disaster management will contributes to the identification of successful practices and the provision of effective urban management of areas prone to war and disaster, with developing appropriate strategies. The main problem was identified with the direct and indirect effects of wars and disasters, with the absence of the appropriate curriculum and strategies to deal with these damages. The research concluded with a set of relevant conclusions and recommendations for it